Tasks, Achievements, and Prospects of The Litvinenko Institute of Physical, Organic and Coal Chemistry of the Nas of Ukraine - Popov, A.F. (Science and Innovation, 2024)
Brief history of the Litvinenko Institute of Physical, Organic and Coal Chemistry of the NAS of Ukraine (IPOCC) has been described. The basic research activities, the most significant fundamental achievements of the Institute, and the most important applied tasks have been reviewed. The IPOCC contribution to the determination of the reasons of man-made environmental catastrophes and the development of methods for their prevention and remedy has been outlined. The IPOCC challenges and prospects under current conditions have been analyzed.